1992
DOI: 10.1007/bf00364592
|View full text |Cite
|
Sign up to set email alerts
|

The role of eggshell and underlying vitelline membrane for normal pattern formation in the early C. elegans embryo

Abstract: The embryo of the nematode Caenorhabditis elegans is surrounded by an inconspicuous inner vitelline membrane and a prominent outer chitinous eggshell proper. We demonstrate that the complete removal of the chitinous eggshell does not interfere with successful development to yield a normal worm. The same result can be obtained when the vitelline membrane is penetrated with laser microbeam irradiation of only the eggshell proper, gently enough to permit its resealing after a while. However, when large holes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 23 publications
4
30
1
Order By: Relevance
“…It has previously been reported that gastrulation does not occur in devitellinized embryos, suggesting that the vitelline envelope might produce a micro-environment required for gastrulation (Schierenberg and Junkersdorf, 1992). However, half of the embryos cultured in that study did not make rhabditin/gut granules, a marker of endoderm differentiation in C. elegans embryos, suggesting that the embryonic culture medium used might not have supported development as well as EGM (see Materials and Methods).…”
Section: Gastrulation Can Occur In Vitromentioning
confidence: 78%
“…It has previously been reported that gastrulation does not occur in devitellinized embryos, suggesting that the vitelline envelope might produce a micro-environment required for gastrulation (Schierenberg and Junkersdorf, 1992). However, half of the embryos cultured in that study did not make rhabditin/gut granules, a marker of endoderm differentiation in C. elegans embryos, suggesting that the embryonic culture medium used might not have supported development as well as EGM (see Materials and Methods).…”
Section: Gastrulation Can Occur In Vitromentioning
confidence: 78%
“…The vitelline layer can be removed from the egg by brief bleaching with sodium hypochlorite without affecting the further development of the embryo (Schierenberg and Junkersdorf, 1992). Embryos after bleaching are neither osmotic sensitive nor permeable to dyes (Fig.…”
Section: 5mentioning
confidence: 99%
“…Two additional layers have recently been observed and defined (Olson et al, 2012; Benenati et al, 2009)(Figure 1). These layers are defined visually through electron micrographs and also by diagnostic biochemical treatments that can remove individual layers from the embryo (Olson et al, 2012; Benenati et al, 2009; Rappleye et al, 1999; Schierenberg and Junkersdorf, 1992). The outermost layer is the vitelline layer (VL) and can be selectively removed by treatment with sodium hypochlorite, leaving the remainder of the eggshell intact.…”
Section: Overview Of the Structure Of The C Elegans Eggshellmentioning
confidence: 99%
“…Although there is a report of some lectin staining enriched in the VL (Bembenek et al, 2007), there is not, to our knowledge, a way to distinguish it from the plasma membrane of the oocyte. This layer can be removed from mitotic embryos using sodium hypochlorite (Schierenberg and Junkersdorf, 1992) without harming their development.…”
Section: Layer One: the Vitelline Layermentioning
confidence: 99%